Interview with Marcelo Beraba: "Society is positively pushing towards balance, plurality and quality of information" - Ramos, Raquel (2022)
Aided by his command of the Spanish language, Folha de Sao Paulo's -the newspaper with the greatest circulation in Latin America- readers representative, Marcelo Beraba, highlights the roles of press in the democratization process which Argentina, Perú and Brazil itself; among others, had undergone. He analyzes and criticizes the excesses carried out on a daily basis by the media and is for greater public participation.